Enhancing Rural Community Assets through Active Transportation Planning: A Case Study of Norway, Maine. - Keeney, Kristine. (2017)
Abstract: Over the last several decades the reduction in transportation options and spread of sprawling land use patterns in rural areas have left rural Americans structurally dependent on their cars with few other safe or practical alternatives. Furthermore, declines in traditional economic sectors has put additional financial burden on rural residents to travel further and spend more of their limited budgets on vehicle ownership and operation to reach outlying employment opportunities. The purpose of this study is to provide small rural towns guidance on connecting valuable community assets with bicycle and pedestrian networks as a means to revitalize their communities. This project also aims to bring a rural perspective to the field of active transportation planning. The Town of Norway, Maine serves as a case study to demonstrate the potential for enhancing existing linkages between community assets in rural towns with connected active transportation facilities. The results of this study reveal that Norway can create connected bicycle and pedestrian networks by prioritizing the repair of existing sidewalk facilities, striping on- street bicycle facilities, and improving safety at intersections where two distinct street types cross. Bicycle and pedestrian networks are proposed by connecting street segments that are in need of new or upgraded infrastructure with the location of valuable community assets. The methodology explored in this thesis can serve as a model to other rural towns interested in applying a data driven approach to active transportation and community development planning.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Mary Davis, and Mark Chase.; Keywords: Transportation planning, and Urban planning.